Allegory and the Matter of Poetics: Dante as a Case Study in Giovanni Boccaccio’s and Leonardo Bruni’s Perspectives - Bertolio, Johnny L. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
The question of whether or not to read poetry through an allegorizing lens had significant implications in the Middle Ages. The identification of allegories in a poetical text was highlighted by early supporters of poetry as the primary means of legitimizing the craft; regardless of whether a poet quoted a pagan god or a mythological figure, the true challenge was to find the real meaning beneath the surface. This approach—one embraced by Giovanni Boccaccio—offered a wealth of samples to the earliest readers of Dante’s Divine Comedy. At the end of the fourteenth century, some humanists started to call into question the theological stance on which the allegorical interpretations were based. In order to promote the autonomous status of poetry, literati of the calibre of Leonardo Bruni maintained that allegory was a double-edged sword. Inspired by Plato’s refusal of allegory, Bruni encouraged the reading of literary texts free from the restrictions of a theoretical superstructure. For proponents of these opposing tendencies, Dante represented a true case study, for he was both a theorist and a poet in his own right and could therefore nourish the reflections formulated by both camps.